STAKEHOLDER PERCEPTIONS AND MODEL OF ENGAGEMENT FOR SUSTAINABLE TOURISM DEVELOPMENT IN ADJARA AUTONOMOUS REPUBLIC (International Journal of Innovative Technologies in Economy, 2021)
As travel and tourism became one of the sectors most affected by the Covid-19 pandemic, the concept of sustainable tourism development becomes inevitable. In order to achieve sustainable development, special value is assigned to stakeholder engagement at all the stages of the development, from the policy formation to the project implementation. The paper analyses the stakeholder perceptions towards the sustainable tourism development based on the example of Autonomous Republic of Adjara, elaboration of necessary directions for practical realization of their engagement in the decision-making process is concluded. The quantitative data needed for research purposes were collected through a structured questionnaire. Respondents' opinions were established on the current state of tourism in the Autonomous Republic of Adjara and the strategy of subsequent development of the industry. The results show that different groups of stakeholders have different perceptions towards different attitudes, some of which are expressed in critical positions. On the basis of research results, the views of different groups of stakeholders is set out to ensure the further steps in the sustainable development of tourism and the stakeholder engagement model in the planning process is proposed.